Efeitos do treinamento aeróbico e de dupla tarefa na mobilidade, marcha, equilíbrio e cognição em idosas da comunidade: um ensaio clínico controlado - Gisele de Cássia Gomes (2014)
Training of a secondary task during gait, whether it is cognitive or motor, may enhance automation, walking performance, and postural control and, thus, minimize the risk of falls influenced by the increased variability of gait patterns. However, the literature is still scarce regarding the influence of dual-task training on changes in gait parameters and cognitive functions. The purpose of this prospective, blinded randomized controlled trial was to compare the short- and long-term effects of gait with dual-task cognitive and motor training (experimental group) with the aerobic training (control group) at the gait stride variability and executive function of independent community-dwelling elderly women. The participants (67 elderly women) were randomly allocated into either experimental or control groups. Both experimental and control groups received 50 minutes/daily training, three times/week over 12 weeks, totaling 36 sessions. At baseline, after 18 and 36 sessions, and 12 weeks after the cessation of the interventions, researchers blinded to group allocations collected the outcome measures. Primary outcome included gait stride variability, which was assessed by the GaitRite® system, during cognitive and motor dual-tasks, at both normal and fast speeds. Secondary outcomes included mobility tests and a battery of global cognitive function, attention, and executive function tests. The analyses showed that the groups were homogeneous regarding their sociodemographic and clinical variables. The results showed that significant improvements were found for speed, cadence, and the time to perform the Timed up and go (TUG) test at usual speed and on execution of motor and cognitive dualtasks for both groups and they remained at follow-up. However, no changes in gait stride variability were observed for both groups after the interventions. Except for the Trail making test B, all cognitive function measures (Addenbrooke's Cognitive Examination- Revised (ACE-R), Codes (WISC-III), and Frontal Assessment Battery (FAB) showed significant improvements after training and these gains were observed for both groups. However, significant improvements in the 20-meter walking test at usual speed and with dual-cognitive task (naming colors) and the Stroop-colors test were found only for the experimental group. The findings demonstrated that both interventions resulted in benefits in most assessed outcomes. It is possible that these benefits were the result of the aerobic component, present in both interventions, and not to the cognitive/ motor training.